Preferences for cultural relic preservation method in Chinese traditional museums / Liu Jun, Maszura Abdul Ghafar and Adlina Ab Halim - Liu, Jun; Abdul Ghafar, Maszura; Ab Halim, Adlina (Faculty of Art and Design, 2025)
Static exhibits in Chinese traditional museums pose challenges in maintaining connections between the public and museum artwork. There is a need for a better exhibition method to stimulate visitors’ monotonous experience of cultural relics and visitors' sense in Chinese museums. The aim of this study is to identify the best preferences for cultural relic preservation methods in Chinese traditional museums. This systematic literature review paper discusses the systematic inferences of cultural relic preservation strategies in Chinese museums, heritage preservation techniques, and the human-exhibition interaction (HEI) concept that could aid the sustainability of cultural heritage interest while conveying cultural heritage-related knowledge in China. This study found that mixed realities (XR) and Human-Exhibition-Interaction (HEI) could facilitate diverse cultural heritage restoration, accuracy and sustainability when adhering to museum exhibitions. The proposed preferences for the cultural relic preservation exhibition method could aid in better visitors’ experience and sense of cultural relics in Chinese museums.